1995
DOI: 10.1002/ar.1092430108
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional organization of the elastic fibres in the rat lung

Abstract: The method we have applied to visualize the elastic fibres of the lung is a unique approach to define the spatial organization of the pulmonary elastic fibres. We have demonstrated here the close relationship between the elastic fibres and the capillaries of the septal alveoli. The arrangement of the interwoven network of elastin and its relationship with the capillaries offers the structural setting for the distending capacity of the alveolar wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Arising from the need to exploit and integrate their distinctly different mechanical properties, in animal tissues, elastic tissue fibers are almost constantly found in close topographical relationship to the collagenous fibers (Elden, 1968;Gosline, 1976;Gosline & French, 1979;Alter, 2004). In the compliant mammalian lung, elastic tissue occurs abundantly and diffusely (Gonçalves et al 1995;Tochima et al 2004). Carton et al (1964) observed that more elastic tissue was present in the lungs of two mammalian species than was theoretically expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arising from the need to exploit and integrate their distinctly different mechanical properties, in animal tissues, elastic tissue fibers are almost constantly found in close topographical relationship to the collagenous fibers (Elden, 1968;Gosline, 1976;Gosline & French, 1979;Alter, 2004). In the compliant mammalian lung, elastic tissue occurs abundantly and diffusely (Gonçalves et al 1995;Tochima et al 2004). Carton et al (1964) observed that more elastic tissue was present in the lungs of two mammalian species than was theoretically expected.…”
Section: Discussionmentioning
confidence: 99%
“…the area containing the air and the blood capillaries, is literally 'suspended' between the axial (A) and peripheral (E) pillars by a dense network of collagen fibers. Gonçalves et al 1995;Maina, 2002;Tochima et al 2004). The corresponding structures of the avian lung have not been investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acinus, elastin is present in the axial backbone of the alveolar ducts and alveolar entrances, as well as in the external sheath of the extra-alveolar microvessels [5][6][7][8]. This axial system is interconnected to the peripheral interstitial system that AFFILIATIONS *Rouen University Hospital, extends through the interlobular septa towards the pleura [8,9].…”
mentioning
confidence: 99%
“…
In mammals it is well known the role of the elastic fibres in the lung development and its fundamental importance in the process of distending and recoil of the organ as a whole [1]. The bird' lungs are compact and virtually non-expansible [2].
…”
mentioning
confidence: 99%